2015
DOI: 10.1128/aac.05148-14
|View full text |Cite
|
Sign up to set email alerts
|

In Silico -Based High-Throughput Screen for Discovery of Novel Combinations for Tuberculosis Treatment

Abstract: There are currently 18 drug classes for the treatment of tuberculosis, including those in the development pipeline. An in silico simulation enabled combing the innumerably large search space to derive multidrug combinations. Through the use of ordinary differential equations (ODE), we constructed an in silico kinetic platform in which the major metabolic pathways in Mycobacterium tuberculosis and the mechanisms of the antituberculosis drugs were integrated into a virtual proteome. The optimized model was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…INDIGO-MTB outperforms existing strategies in terms of throughput. The largest studies of MTB have so far analyzed up to 200 unique drug combinations (36). Here, we have estimated outcomes for 13,366 pairwise and 721,764 three-way combinations of 164 drugs with significant accuracy based on our prospective validation.…”
Section: Discussionmentioning
confidence: 99%
“…INDIGO-MTB outperforms existing strategies in terms of throughput. The largest studies of MTB have so far analyzed up to 200 unique drug combinations (36). Here, we have estimated outcomes for 13,366 pairwise and 721,764 three-way combinations of 164 drugs with significant accuracy based on our prospective validation.…”
Section: Discussionmentioning
confidence: 99%
“…INDIGO-MTB outperforms existing strategies in terms of throughput. The largest studies in MTB have so far analyzed up to two hundred unique drug combinations (37). Here, we have estimated outcomes for 13,366 pairwise and 721,764 three-way combinations of 164 drugs with significant accuracy based on our prospective validation.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, we have demonstrated the importance of low pH screens by selecting PZA-hybrid molecules in-vitro [ 69 ]. Recently, PZA was also reported to enhance the cidality of various combinations of existing drugs [ 70 ]and is an integral component of emerging novel combinations in the clinic like PAMZ (PA-824, Moxi, PZA), in STAND (Shortening Treatment by Advancing New Drugs, www.clinicaltrial.com ) clinical trial. Our findings unequivocally suggest that anti-TB activity in the low pH environment may be predictive of in-vivo tuberculocidality, especially for the acute phase of infection.…”
Section: Discussionmentioning
confidence: 99%